Résumé du dialogue : Développer un programme de dépistage du diabète de type 1 au Canada - Wu, N; Bain, T; Hayeems, R; Wilson, MG (My University, 2024)
Canadian Institutes of Health Research (CIHR) and the Juvenile Diabetes Research Foundation via a grant to the Hospital of Sick Children (SickKids) for The Canadian Population Screening for Risk of Type 1 Diabetes (CanScreen T1D) Research Consortium
Keywords: Type 1 diabetes; program; Canada